1990
DOI: 10.1177/38.8.2114440
|View full text |Cite
|
Sign up to set email alerts
|

Localization of carbonic anhydrase in identified glial cells of the leech central nervous system: application of histochemical and immunocytochemical methods.

Abstract: We localized the enzyme carbonic anhydrase (CA) in frozen sections of the leech (Hirudo medicinalis) central nervous system by two histochemical techniques and the indirect immunofluorescence technique. Hansson's cobalt precipitation method and the use of 1-dimethylamino-naphthalene-5-sulfonamide (DNSA) to build a fluorescent enzyme-substrate complex showed that glial cells are the sites of CA activity in the leech. Neuropil and connective glial cells surrounding the axons had strong CA activity, whereas packe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The ganglia and connectives show an identical organization, and they contain neuranes and glial cells that can be identified and distinguished according to their location and electrical properties (Schlue et ale 1980;Riehl and Schlue 1990). …”
Section: Te Leech Prep~rationmentioning
confidence: 99%
“…The ganglia and connectives show an identical organization, and they contain neuranes and glial cells that can be identified and distinguished according to their location and electrical properties (Schlue et ale 1980;Riehl and Schlue 1990). …”
Section: Te Leech Prep~rationmentioning
confidence: 99%
“…Therefore, CA is an essential factor in acid-base balance and a transport mechanism for CO, and CA was localized in frozen sections of the leech CNS. 36 Hansson's cobalt precipitation method and the use of DNSA to build a fluorescent enzyme-substrate complex showed that glial cells are the sites of CA activity in the leech. Neuropile and connective glial cells surrounding the axons had strong CA activity, whereas packet glial cells, which surround neuron cell bodies, and neurons themselves remained unstained.…”
Section: Localization Of Carbonic Anhydrase By Andplication Of Histochementioning
confidence: 99%
“…The ganglia of the leech nervous system show an identical organization, and they contain glial cells that can be identified and distinguished according to their location and electrical properties (Riehl and Schlue, 1990; . Six packet glial cells in each ganglion surround the neuron cell bodies, and two neuropile glial (NG) cells enclose the neuron processes and synaptic regions.…”
Section: Introductionmentioning
confidence: 99%